2011
DOI: 10.1002/dvdy.22670
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological study of palatal shelf elevation during murine secondary palate formation

Abstract: During mammalian secondary palate development, the palatal shelves undergo dramatic morphological changes to elevate from a vertical to a horizontal plane in the oral-nasal cavity. We found that E14.5 mouse embryos displayed marked variations in shelf morphology that represent various intermediate states of the elevation process. With these variations, we reconstructed the sequence of shelf morphological changes that take place during the elevation process and discovered distinct patterns in different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 11 publications
8
76
0
Order By: Relevance
“…3C,D), supporting the hypothesis of Walker and Fraser that remodeling and horizontal outgrowth from the medial wall of the vertical palatal shelves give rise to the 'elevated' palatal shelves (Walker and Fraser, 1956). A recent histomorphological reexamination of this process (Yu and Ornitz, 2011) is in general…”
Section: Patterning Along the Mediolateral Axismentioning
confidence: 99%
See 1 more Smart Citation
“…3C,D), supporting the hypothesis of Walker and Fraser that remodeling and horizontal outgrowth from the medial wall of the vertical palatal shelves give rise to the 'elevated' palatal shelves (Walker and Fraser, 1956). A recent histomorphological reexamination of this process (Yu and Ornitz, 2011) is in general…”
Section: Patterning Along the Mediolateral Axismentioning
confidence: 99%
“…REVIEW Development 139 (2) agreement with the report of Walker and Fraser but presented a refined timing for palatal shelf remodeling along the AP axis. Whereas Walker and Fraser described palatal shelf reorientation proceeding in a wave-like manner from posterior to anterior (Walker and Fraser, 1956), Yu and Ornitz showed histological evidence that horizontal outgrowth from the medial wall of the vertically oriented palatal shelves starts from the mid-posterior region, and palatal shelf reorientation occurs in a dynamic and regionalized manner along the AP axis (Yu and Ornitz, 2011). Although the forces that drive palatal shelf elevation are still incompletely understood, recent progress has been made in identifying the genetic factors that control this event.…”
Section: Reviewmentioning
confidence: 99%
“…This movement is known as palatal shelf elevation. Once in a horizontal position, the bilateral palatal shelves grow toward each other, establish contact along the midline, and fuse (Bush and Jiang, 2012;Ferguson, 1977Ferguson, , 1988Iwata et al, 2011;Yu and Ornitz, 2011). Alterations in any of these steps may lead to a cleft palate, which is one of the most common human birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in any of these steps may lead to a cleft palate, which is one of the most common human birth defects. The elevation process is not well understood, but may involve a heterogeneous mechanism along the anteroposterior (AP) axis (Yu and Ornitz, 2011). The anterior portions of the palatal shelves seem to elevate by rotating, whereas the middle and posterior portions change their orientation via a remodeling mechanism (Bush and Jiang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid rotation and remodeling of the palatal shelf occur during palatal shelf elevation (Bush and Jiang 2012). Some studies have demonstrated that the different regions of the palatal shelf along the anteroposterior (AP) axis employ distinct mechanisms during palatal shelf elevation (Hilliard et al 2005;Yu and Ornitz 2011). The mid-palate region elevates mainly by means of rotation and medial shelf elongation (Chou et al 2004).…”
Section: Introductionmentioning
confidence: 99%